2000
DOI: 10.1007/s004360050684
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity, predilection sites, and freeze tolerance of Trichinella spp. in experimentally infected sheep

Abstract: A total of 36 sheep in groups of 4 were inoculated with 9 isolates of Trichinella and euthanized after 10 weeks. Thereafter, numbers of muscle larvae were determined in 13 different muscles/muscle groups. Muscle larvae were found in high numbers in all four sheep inoculated with T. spiralis, in lower numbers in two sheep inoculated with T. pseudospiralis (USA isolate), and in very low numbers in one sheep inoculated with T. pseudospiralis (USSR isolate) and one inoculated with T. britovi. In infections of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Chadee and Kick (1982) reported that all larvae of T. spiralis were alive after 14 months in a frozen state. Muscle larvae of T. spiralis remain infective even after exposure to temperatures of 5 and −5°C for several weeks (Theodoropoulos et al 2000;von Koller et al 2001;Malakauskas and Kapel 2003). The present results show that viability was still nearly 100% even after incubating the larvae for 3 days at 0°C.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Chadee and Kick (1982) reported that all larvae of T. spiralis were alive after 14 months in a frozen state. Muscle larvae of T. spiralis remain infective even after exposure to temperatures of 5 and −5°C for several weeks (Theodoropoulos et al 2000;von Koller et al 2001;Malakauskas and Kapel 2003). The present results show that viability was still nearly 100% even after incubating the larvae for 3 days at 0°C.…”
Section: Discussionsupporting
confidence: 62%
“…The worldwide distribution in geography and a wide range of hosts suggests that these infective larvae have high tolerance to various kinds of stress, for example, temperature and decaying tissues, during its transition from host to host. The L1 larvae remain infective even after exposure to −5°C for 4 weeks (Theodoropoulos et al 2000;Malakauskas and Kapel 2003), or even during the degradation of infected tissues (von Koller et al 2001). This parasite can escape host immune attack and survive within a muscle cell for years.…”
Section: Introductionmentioning
confidence: 99%
“…We detected a higher larval burden than other authors (Table 3). Theodoropoulos et al (2000) and Reina et al (1996) used sheep and goats, respectively, at the same age (2 months old) and with the same infective dose (10,000 larvae per animal) as in our experiment. The differences can be caused by several reasons, such as individual variability and differences in the Trichinella strain that was used for experimental infection.…”
Section: Discussionmentioning
confidence: 98%
“…In Europe, no outbreak of human trichinellosis has been attributed to the consumption of ruminant meat, but in Asia, sheep, cow, and wild moufflon (Ovis musimon) are occasional sources of infection (Zhu and Niu 1988;Liu and Boireau 2002). There have been reports on the following studies in experimentally infected, nonspecific ruminant hosts: (Smith and Snowdon 1988;Smith et al 1989;Tomašovičová et al 1991;Pajerský et al 1996;Reina et al 1996;Oksanen et al 2000;Theodoropoulos et al 2000).…”
Section: Introductionmentioning
confidence: 90%
“…larvae in muscle tissue have included laboratory assessments of parasite tolerance to cold and freezing temperatures, "wet-curing" and seasoning (Theodoropoulos et al 2000;Malakauskas and Kapel 2003;Hill et al 2007;MedinaLerena et al 2009). Other authors have also evaluated the same parameters during tissue exposition to a constant temperature and humidity (Von Köller et al 2001), and studies on the tolerance to freezing temperature (−5°C) of different isolates of Trichinella nativa from fox tissues were made by Davidson et al (2008).…”
Section: Introductionmentioning
confidence: 99%